2020
DOI: 10.7717/peerj.8276
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biological pathways and genes associated with neurogenic heterotopic ossification by text mining

Abstract: Background Neurogenic heterotopic ossification is a disorder of aberrant bone formation affecting one in five patients sustaining a spinal cord injury or traumatic brain injury (SCI-TBI-HO). However, the underlying mechanisms of SCI-TBI-HO have proven difficult to elucidate. The aim of the present study is to identify the most promising candidate genes and biological pathways for SCI-TBI-HO. Methods In this study, we used text mining to generate potential explanations for SCI-TBI-HO. Moreover, we employed se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another study examined mesenchymal stromal cells derived from individuals with SCI or traumatic brain injury (TBI). The authors identified increased GDF15 secretion into cell lysate, indicative of a widespread cell stress response (Zhang et al, 2020). This induction was also reported in injured rodent CNS and PNS tissue in response to cryolesion (Schober et al, 2001) and sciatic nerve crush (Wang et al, 2015) respectively.…”
Section: Elevated Gdf15 Is Associated With Neurodegenerative Disease ...mentioning
confidence: 59%
“…Another study examined mesenchymal stromal cells derived from individuals with SCI or traumatic brain injury (TBI). The authors identified increased GDF15 secretion into cell lysate, indicative of a widespread cell stress response (Zhang et al, 2020). This induction was also reported in injured rodent CNS and PNS tissue in response to cryolesion (Schober et al, 2001) and sciatic nerve crush (Wang et al, 2015) respectively.…”
Section: Elevated Gdf15 Is Associated With Neurodegenerative Disease ...mentioning
confidence: 59%
“…The pathophysiology of OLF and SOP may be closely associated with a variety of cytokines or chemokines involved with inflammation and immunology, including NFKBIA, TNFRSF11, IL-10, and CCL2. CCL2 has been strongly linked to traumatic brain injury, where it may contribute to neurogenic heterotopic ossification, and it can also be secreted by macrophages, where it may play an important role in osteoblast development in heterotopic ossification (HO) [ 29 ]. Additionally, a number of studies have hypothesized that CCL2 was an osteoporosis and osteopenia risk factor [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neurogenic heterotopic ossification (NHO) can occur after the spinal cord injury (SCI) or traumatic brain injury (TBI). Other clinical conditions, such as cerebral stroke, anoxia, and non-traumatic myelopathies, can also attribute to NHO [ 32 , 33 , 34 ]. The incidence of NHO in spinal cord injury (40%–50%) was reported to be higher than in traumatic brain injury patients (8%–23%).…”
Section: Heterotopic Ossification As a Clinical Issuementioning
confidence: 99%